As áfricas no ensino de História da Rede Municipal Educação de Florianópolis - Abreu, Ticiane Caldas de (2020)
The current research aims to problematize the experiences of the implementation of the Federal Law number 10.639/03, within the African studies’ field in Santa Catarina, Brazil, glistering how such approaches to the contents related to African and Afro-Brazilian History and Culture are being disseminated in elementary education of the public schools in Florianópolis/SC. Specifically, the research seeks to understand which ideas about the African continent permeates the imaginary of 8th and 9th grade students from the Basic Education schools Beatriz de Souza Brito and Doutor Paulo Fontes, thus, turning possible the contribution to the knowledge chain related to African studies in Brazil, especially in Santa Catarina